2014
DOI: 10.1111/radm.12083
|View full text |Cite
|
Sign up to set email alerts
|

Formal integration archetypes in ambidextrous organizations

Abstract: Research suggests that organizational ambidexterity, an organization's capacity to pursue both exploratory and exploitative activities, is critical to firm innovation and performance. Extant research primarily emphasizes several firm-level informal integration mechanisms, such as creating a common vision and relying on social integration, for integrating structurally ambidextrous units. Research has largely ignored, however, the formal mechanisms by which organizations have integrated such units. In this induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 45 publications
1
48
0
Order By: Relevance
“…Research on organizational ambidexterity (Junni et al, ; Junni et al, ) also provides some insights into these findings. An organization's capacity to pursue both exploratory and exploitative forms of innovation and to vary the balance according to changes in market opportunities and competitor behavior is critical to firm performance and survival (Chen and Kannan‐Narasimhan, ). Our study suggests that mutually exclusive innovation strategies/processes can be successfully reconciled, potentially explaining aspects of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Research on organizational ambidexterity (Junni et al, ; Junni et al, ) also provides some insights into these findings. An organization's capacity to pursue both exploratory and exploitative forms of innovation and to vary the balance according to changes in market opportunities and competitor behavior is critical to firm performance and survival (Chen and Kannan‐Narasimhan, ). Our study suggests that mutually exclusive innovation strategies/processes can be successfully reconciled, potentially explaining aspects of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate cross‐fertilization between exploitative and exploratory structures without cross‐contamination (O’Reilly and Tushman, ), following the call for research by Raisch (), Lavie et al (), Gassmann et al (), and O’Reilly and Tushman (), recent research in ambidexterity has focused on the management of the exploration–exploitation interface. Of particular interest are integration mechanisms (or tactics) to loosely couple exploitation and exploration (Jansen et al, ) as well as related transition modes for ultimately reintegrating radical innovations back into the core business (Gassmann et al, ; Chen and Kannan‐Narasimhan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the role of senior management is crucial to deal with integration challenges of exploration and exploitation and devise strategic measures for reconciling them at the organizational level (Burgers, Jansen, Van den Bosch, Volberda, 2008, Fourné, et al, 2019Jansen et al 2009;Mom, Van Den Bosch, & Volberda, 2009). In other words, the integrative mechanisms required in pursuing structural ambidexterity to large extent a leadership issue than mere separation of units (Chen & Kannan-Narasimhan, 2015;Gassmann, Widenmayer & Zeschky, 2012;Hansen;Wicki & Schaltegger, 2018;Heracleous, Papachroni, Andriopoulos & Gotsi, 2017;Jansen, George, Van den Bosch & Volberda, 2008;Nemanich & Vera, 2009;O'Reilly & Tushman, 2011;Smith & Tushman, 2005). So far, pertaining to dual structure or structural differentiation's effect on organizational ambidexterity yield mixed results with positive (e.g.…”
Section: Structural Ambidexteritymentioning
confidence: 99%
“…Further, it has been argued that structural separation or differentiation approach can lead to the disjunction of different units, a failure to manoeuver efforts carried out by the units, and inability to take advantage of potential synergies of different units (Agostini et al, 2016;Asif, 2017). Further, structural differentiation can cause self-centered behaviors, where managers of different units may perceive direct competition with other units run for scarce resources (Asif, 2017;Chen & Kannan-Narasimhan, 2015;Gassmann et al, 2012). To mitigate such challenges, it has been suggested that behavioral integration in teams could be productive to reconcile conflicting expectations of different units that can translate antagonistic demands into a workable strategy (Fourné et al, 2019;Jansen et al, 2009).…”
Section: Existing Discrepancies In Structural Differentiation Approachmentioning
confidence: 99%
See 1 more Smart Citation